2004
DOI: 10.1080/14992020400050050
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of hearing aid fitting for older people with hearing impairment and their significant others

Abstract: As hearing impairment affects communication, it seems intuitive that both the person with hearing impairment and the significant other (SO) will experience effects as a result of the impairment and subsequent rehabilitation. The present study examined the effect that hearing impairment and aural rehabilitation has on the person with hearing impairment and the SO's quality of life (QOL). Ninety-three people with hearing impairment completed a measure of hearing-specific QOL (Hearing Handicap Inventory for the E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
152
3
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(172 citation statements)
references
References 30 publications
12
152
3
5
Order By: Relevance
“…The psychometric results for the HHIE questionnaire were consistent with what has been reported in previous studies that used the paper format of the questionnaire (Stark and Hickson 2004;Öberg et al, 2007). A significant main effect of format showed that the participants in general rated a higher score of 3.9 points on a scale of 100 in the internet format than in the paper-and-pencil version.…”
Section: Questionnaire Format Comparisonsupporting
confidence: 80%
“…The psychometric results for the HHIE questionnaire were consistent with what has been reported in previous studies that used the paper format of the questionnaire (Stark and Hickson 2004;Öberg et al, 2007). A significant main effect of format showed that the participants in general rated a higher score of 3.9 points on a scale of 100 in the internet format than in the paper-and-pencil version.…”
Section: Questionnaire Format Comparisonsupporting
confidence: 80%
“…One of their Wndings was that a more severely impaired hearing loss caused greater problems with hearing aids. In a study after the outcome of hearing-aid Wtting, Stark and Hickson [16] also found a relationship between self-reported hearing disability and degree of hearing impairment. They measured disability with the Hearing Handicap Inventory for the Elderly (HHIE) [20] before and after hearing-aid Wtting and found a signiWcantly greater reduction in HHIE-scores for participants with a three-frequency average (3-FA) hearing loss of greater than 35 dB, when compared to the reduction measured for those with a 3-FA hearing loss of less than 25 dB.…”
Section: Discussionmentioning
confidence: 97%
“…This is the subject of previous and on-going research (Stark & Hickson, 2004;Kramer et al, 2005;Knudsen et al, 2010Knudsen et al, , 2012Meyer et al, 2014;Ekberg et al, 2015). Although practical support was offered to all patients, this related solely to support available from hearing services.…”
Section: Discussionmentioning
confidence: 99%